A Liquid Metal Based Multimodal Sensor and Haptic Feedback Device for Thermal and Tactile Sensation Generation in Virtual Reality (Adv. Funct. Mater. 39/2021). (24th September 2021) - Oh, Jinhyeok; Kim, Suin; Lee, Sangyeop; Jeong, Seongmin; Ko, Seung Hwan; Bae, Joonbum
Abstract : Haptic Feedback Devices In article number 2007772, Seung Hwan Ko, Joonbum Bae, and co‐workers develop multimodal sensing and feedback glove, which can measure finger movements and provide vibro‐haptic and thermo‐haptic feedback simultaneously, using soft, stretchable, lightweight, and compact sheets manufactured by direct ink writing of a liquid metal, eutectic gallium‐indium (eGaIn). The resulting glove allows users to feel the contact status and different temperatures under various virtual reality environments.